Thymic humoral factor (THF) therapy in a patient with Di-George syndrome - Ersoy, Fügen; Sanal, Özden; Yeğin, Olcay; Berkel, A. İzzet and Çağlar, Melda (The Turkish Journal of Pediatrics, 1982)
The case of a 17-day-old boy, diagnosed as having DiGeorge syndrome with hypoparathyroidism, typical facial features, cell-mediated immune deficiency, normal levels of serum immunoglobulins, normal antibody response and low level of circulating thymic hormone, is presented. After treatment with 55 doses of THF, the patient showed clinical improvement with in vitro and in vivo correction of the tests for cell-mediated immunity.